2016
DOI: 10.1155/2016/6294030
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Liver Oil ofEchinorhinus brucus(Bramble Shark) and Its Cytotoxic Evaluation on Neuroblastoma Cell Lines (SHSY-5Y)

Abstract: The objective of the present study was to characterize the liver oil extracted from the deep sea shark, Echinorhinus brucus, caught from Central Indian Ocean and to evaluate its cytotoxic effect on neuroblastoma cell line (SHSY-5Y). Characterization of liver oil of Echinorhinus brucus revealed the presence of palmitic acid (15%), oleic acid (12%), stearic acid (8%), docosahexaenoic acid (DHA) (18%), and eicosapentaenoic acid (EPA) (16%). It was also found to be a good source of squalene (38.5%) and fat soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…In contrast, another study using liver oil extracted from deep sea shark (Echinorhinus brucus) showed a dose-dependent cytotoxic effect in neuroblastoma cells (SH-SY5Y) following a 48-hour treatment [49]. The cytotoxic effect, as shown by an MTT assay, resulted in over 90% cell death at concentrations of 5-100 µg, which can be attributed to the high concentration of squalene (38.4%) in this oil [49]. Squalene has been promoted as having cell protective effects, which may also reduce the side effects of chemotherapy [53].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast, another study using liver oil extracted from deep sea shark (Echinorhinus brucus) showed a dose-dependent cytotoxic effect in neuroblastoma cells (SH-SY5Y) following a 48-hour treatment [49]. The cytotoxic effect, as shown by an MTT assay, resulted in over 90% cell death at concentrations of 5-100 µg, which can be attributed to the high concentration of squalene (38.4%) in this oil [49]. Squalene has been promoted as having cell protective effects, which may also reduce the side effects of chemotherapy [53].…”
Section: Discussionmentioning
confidence: 86%
“…Previous reports revealed that SLO, specifically Greenland Shark (Somniosus microcephalus) liver oil increase IFN-γ with subsequent enhancement of cellular immunity and increase in CD8+ lymphocytes accompanied by a decrease in tumor size. In contrast, another study using liver oil extracted from deep sea shark (Echinorhinus brucus) showed a dose-dependent cytotoxic effect in neuroblastoma cells (SH-SY5Y) following a 48-hour treatment [49]. The cytotoxic effect, as shown by an MTT assay, resulted in over 90% cell death at concentrations of 5-100 µg, which can be attributed to the high concentration of squalene (38.4%) in this oil [49].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The excessive cytoplasmic accumulation of olefin oils such as squalene and terpene inflict toxic effects and metabolic stress on the yeast cell [43,44]. However, lipid droplets in yeast can only store small quantities of olefin oil due to the tight regulation of their biogenesis [45,46].…”
Section: Optimization Of Squalene Overproduction Via Overexpression Omentioning
confidence: 99%
“…When sharks are captured, they must be gutted, washed to avoid microbial contamination, placed in polyethylene bags, marked with the date of capture and provenance, then kept in an ice bath at a temperature between 1-5 °C until fishing boats arrive at the port, 20 then quickly freeze and store at a temperature below -18 ⁰C until use. [38][39][40] As soon as possible, the livers should be homogenized and removed at the lowest possible temperature, it is recommended not to exceed 20 ⁰C. 39 In this circumstance, the main danger is a loss of components of unsaturated fatty acids through the autoxidation of these.…”
Section: Preparation and Storagementioning
confidence: 99%